The relationship between ethical climate and work ethics of employees in Central Plastic Industry Sdn. Bhd. - Lam, Jie Rui, 1995-, author; Mohd. Koharuddin Mohd. Balwi, 1969-, supervisor; Fakulti Sains Sosial & Kemanusiaan. Sekolah Pembangunan Sumber Manusia & Psikologi (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper(Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2019